Bidirectional mRNA transfer between Cuscuta australis and its hosts - Li, Tao; Deng, Yunshuang; Huang, Jiaquan; Liang, Jiayin; Zheng, Yongqin; Xu, Qian; Fan, Shuting; Li, Wenting; Deng, Xiaoling; Zheng, Zheng (Frontiers in Plant Science, 2022)
The holoparasitic dodder (Cuscuta spp.) is able to transfer mRNA and certain plant pathogens (e.g., viruses and bacteria) from the host plant. “Candidatus Liberibacter asiaticus,” the phloem-limited causative agent of citrus Huanglongbing, can be transferred from citrus to periwinkle (Catharanthus roseus) mediated by dodder. However, characterization of mRNA transport between dodder and citrus/periwinkle remains unclear. In this study, we sequenced transcriptomes of dodder and its parasitizing host, sweet orange (Citrus sinensis “Newhall”) and periwinkle (Catharanthus roseus), to identify and characterize mRNA transfer between dodder and the host plant during parasitism. The mRNA transfer between dodder and citrus/periwinkle was bidirectional and most of the transfer events occurred in the interface tissue. Compared with the citrus–dodder system, mRNA transfer in the periwinkle–dodder system was more frequent. Function classification revealed that a large number of mRNAs transferred between dodder and citrus/periwinkle were involved in secondary metabolism and stress response. Dodder transcripts encoding proteins associated with microtubule-based processes and cell wall biogenesis were transferred to host tissues. In addition, transcripts involved in translational elongation, plasmodesmata, and the auxin-activated signaling pathway were transmitted between dodder and citrus/periwinkle. In particular, transcripts involved in shoot system development and flower development were transferred between the host and dodder in both directions. The high abundance of dodder-origin transcripts, encoding MIP aquaporin protein, and S-adenosylmethionine synthetase 1 protein, in citrus and periwinkle tissues indicated they could play an important biological role in dodder–host interaction. In addition, the uptake of host mRNAs by dodder, especially those involved in seed germination and flower development, could be beneficial for the reproduction of dodder. The results of this study provide new insights into the RNA-based interaction between dodder and host plants.